Schumpeter and Max Weber: Comment - Hansen, Niles M. (Quarterly Journal of Economics, 1966)
Journal Article Schumpeter and Max Weber: Comment Get access Niles M. Hansen Niles M. Hansen University of Texas, University of Paris Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 80, Issue 3, August 1966, Pages 488–491, https://doi.org/10.2307/1880736 Published: 01 August 1966